The PACE Trial’s GET Manual for Therapists Exposes the Fixed Incremental Nature of Graded Exercise Therapy for ME/CFS - Mark Vink; Katarzyna Partyka-Vink (Life)
The British National Institute for Health and Care Excellence (NICE) published its updated guidelines for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) in October 2021. NICE concluded, after an extensive review of the literature, that graded exercise therapy (GET) is harmful and should not be used, and that cognitive behavioural therapy (CBT) is only an adjunctive and not a curative treatment. An article by White et al., which is written by 51 researchers, claims that there are eight anomalies in the review process and the interpretation of the evidence by NICE. In this article, we reviewed the evidence they used to support their claims. Their three most important claims are that NICE redefined the disease, that CBT and GET are effective, and that fixed incremental increases are not part of GET. However, our analysis shows that the disease was not redefined by NICE. Instead, it was redefined in the 1990s by a group of doctors, including a number of authors of White et al., when they erased the main characteristic of the disease (an abnormally delayed muscle recovery after trivial exertion, which, over the years, has evolved into post-exertional malaise) and replaced it with chronic disabling severe fatigue. Their own studies show that CBT and GET do not lead to a substantial improvement of the quality-of-life scores or a reduction in CFS symptom count, nor do they lead to objective improvement. Also, both treatments have a negative instead of a positive effect on work and disability status. Moreover, a recent systematic review, which included one of the authors of White et al., showed that ME/CFS patients remain severely disabled after treatment with CBT. Our analysis of, for example, the PACE trial’s GET manual for therapists exposes the fixed incremental nature of GET. Why the authors are not aware of that is unclear because eight of them were involved in the PACE trial. Three of them were centre leaders and its principal investigators, four others were also centre leaders, and another one was one of the three independent safety assessors of the trial. Moreover, many of these eight authors wrote, or were involved in writing, this manual. In conclusion, our analysis shows that the arguments that are used to claim that there are eight anomalies in the review process and the interpretation of the evidence by NICE are anomalous and highlight the absence of evidence for the claims that are made. Furthermore, our analysis not only exposes the fixed incremental nature of GET, but also of CBT for ME/CFS.